Evaluation on the performances of adsorption desalination employing functionalized metal-organic frameworks (MOFs) - Han, Bo (2023)
This study focuses on a comprehensive study of MOFs (metal-organic frameworks) plus water systems for adsorption desalination applications. The paper first deals with the modification of parent MOFs such as aluminium fumarate, MOF-801 (Zr) and UiO-66 (Zr) employing MOFs functionalization, alkali ion doping and impregnation of zeolites, and secondly, we focus on their characterizations for understanding both structural and thermal stabilities. Later, water adsorption on these parents and modified MOFs are investigated for a wide range of pressure (0 < P/Ps < 1.0) and temperature (30–80 °C). Based on experimentally confirmed isotherms, kinetics and MOFs characteristics data, the performance factors such as SDWP (specific daily water production) and PR (performance ratio) are evaluated for various regeneration temperature (55–80 °C) and cycle time (100–1000 s). Furthermore, the water adsorption characteristics are applied to calculate the entropy flow and generation for each component of AD system. The SDWP is also calculated from the concepts of temperature – entropy diagram. It is found that both OH-UiO-66 (Zr) and 5 %Li-Al-FumMOFs provide promising SDWP (>34 m3 /tonne of MOFs/day) and 5 %Li-Al-Fum shows minimum entropy generation.